Short Message Services and their impact on society - Puclla-Pillco, Daivie B. (2022)
In this article, the analysis of models, procedures, type of technologies and work platforms of various social programs that use SMS (Short Message Services for its acronym in English) which provide or make known various services and benefits to through sending text messages. SMS are among the most used services by mobile phone users due to their low cost, ease of use, speed of implementation and communication performance. Likewise, the reliability of SMS messages should be highlighted, considering that they are text messages, they are fast, profitable due to the low cost for the user and the results can be analyzed very quickly. Other advantages that its use implies are: it is efficient, easy to configure and has an almost immediate impact on the responses and service opportunities for customers and/or users.